Selection of Xilose-Fermenting Yeast Strains - Silva,Rosimeire Oenning da (2016)
ABSTRACT In Brazil, ethanol is obtained by fermentat of sugar cane juice using Saccharomyces cerevisiae. The cane juice extraction generates the bagasse that has been used for obtaining generation biofuel. However, the sugarcane bagasse has 30% pentose that cannot be fermented to ethanol by S. cerevisiae. Thus the aim of this study was to isolate a yeast able to ferment xylose to ethanol. Samples of cane juice and flowers were used for the isolation of 165 strains that were then screened for ethanol production using plate testing. Among them, the ethanol positive strains Wickerhamomyces anomalus, Schizosaccharomyces pombe and Starmerella meliponinorum were selected for a xylose fermentation assay, using a semi-synthetic and bagasse hydrolysate as must. S. meliponinorum and S. pombe produced 0.63 and 2.7 gL-1 of ethanol, respectively, from xylose in a semisynthetic medium. In the medium consisting of bagasse hydrolysate must, 0.67 and 1.1 gL-1 of ethanol were obtained from S. meliponinorum and S. pombe, respectively. All the yeasts produced xylitol from xylose in the semisynthetic medium and S. meliponinorum was that which produced the highest quantity (14.5 g L-1).